EFFECTIVENESS OF A RECOMBINANT VACCINE BASED ON RNA2 CAPSID PROTEIN AGAINST NERVOUS NECROSIS VIRUS IN HYBRID GROUPER - Ketut Mahardika; Indah Mastuti; Sudewi Sudewi; Des Roza; Zafran Zafran (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2020)
Nervous Necrosis Virus (NNV) is a devastating viral disease in marine aquaculture, causing significant economic losses worldwide, including in Indonesia. The virus mainly infects larvae and juveniles of marine fishes. This study aimed to determine the effectiveness of a recombinant vaccine from betanodavirus coat proteins expressed in Escherichia coli fish against NNV infection in hybrid grouper. An RNA2 capsid protein was selected and used as the recombinant vaccine. NNV-RNA2 gene was inserted into the protein expression system vector of pET SUMO and cloned in cells of bacteria Escherichia coli strain BL-21. The results of blast homology analysis exhibited that the amino acid sequence of the NNV-RNA2 showed high similarity with Lates calcarifer encephalitis viral coat protein gene. E. coli expressing NNV-RNA2 protein was inactivated using 0.03% formalin and mechanically inactivated by freeze-thaw and sonication methods. The inactivated recombinant E. coli vaccine was then injected intramuscularly into hybrid grouper juveniles (single vaccine). Subsequently, the juveniles were challenged with NNV at 7, 14, and 21 dpv (days post-vaccination). Injection of 0.1 mL sterile PBS served as the control. Single vaccine applications using formalin-inactivated vaccines resulted in higher antibody titers than those of mechanically-inactivated vaccines. Both vaccines were only able to increase antibody titer up to 7 dpv. Therefore, re-vaccination (booster vaccine) was done on day-10 after the first vaccination using a formalin-inactivated vaccine. The booster vaccine could protect hybrid grouper against NNV (P<0.05) at four weeks post-vaccination. However, the mortality of vaccinated and control fish was not significantly different (P>0.05) after challenged with NNV for six weeks after. This recombinant vaccine has the potential to be developed into a polyvalent vaccine by combining viral and other bacterial vaccines in future research.